Managing Mutrashmari through Ayurvedic Drugs - II: Shwet Parpati - Suden, Akshay (International Research Journal of Ayurveda & Yoga, 2020)
This paper presents the findings of a clinical trial conducted in the suburbs of Jammu ( Jammu & Kashmir State ) to assess the efficacy of shwet parpati therapy – an Ayurvedic mineral compound, on a random sample of ten mutrashmari patients. In all there were 14 calculi sites, of which 8 (57 %) were in Kidney and 6 (43 %) were in Ureter. There were 6 (43 %) calculi sites which were uni-lateral and single, 2 sites (29 %) were multiple (double) but unilateral while the remaining 2 (28 %) were bi lateral and single in each kidney. All the calculi cases were in the size range of 4 – 8 mm. The shwet parpati therapy completely cured 4 (28.6 %) of the cases. It markedly improved 5 (35.7 %) cases and improved 3 (21.4 %) of the cases. Only 2 (14.3 %) cases did not show significant response to therapy. The overall rating of the therapy was 1.8. In all there were 8 Kidney stones. Two stones (25.0 %) were completely cured, 3 (37.5 %) were markedly improved. Two (25.0 %) were improved towards curing but 1 (12.5 %) did not respond to the therapy. Overall rating of the therapy was 1.8. There were 6 Ureter stones. Two (33.3 %) each, were cured and markedly improved. One (16.7 %) was improved and the remaining 1 (16.7 %) did not respond to therapy significantly. Overall rating of the therapy towards Ureter Stones was 1.8. kaphaja was represented in 4 (40 % ) of the patients, followed by 3 (30 %) in vataja and 3 (30 %) in pittaja ashmari. This shows the dominance of kaphaja type of ashmari in the study area. There were 8 stones with kaphaja ashmari, out of which 3 (37,5 %) were completely cured, 4 (50%) stones were markedly improved and 1 (12.5%) showed improvement in symptoms. The therapy depicted good overall rating of 2.3. There were 3 stones of pittaja ashmari type and no complete cure was noticed in this case. Two (66.7 %) cases were markedly improved and the remaining 1 (33.3 %) showed improvement. The overall rating was 1.7. There were 4 stones in vataja ashmari cases, out of which 2 (50.0 %) were completely cured, while the remaining 2 (50.0 %) stones did not respond to the therapy significantly. The therapy depicted an overall rating of 1.5. The effect of shwet parpati was highly significant on basti vedana (58.3 %), nabhi vedana (58.0 %), mehan vedana (55.6 %) and on gomeda prakasam (50.0 %). The effect was also significant on mutradhara sanga (71.4 %) and atiavila mutrata (71.4 %). While non-significant effect was observed on sarudhiramutrata ( 66.7 %) and sevani vedana (8.3 %). Nausea & vomiting and fever parametres did not affect the sample cases. The effect was highly significant on burning micturition (66.7 %), tenderness at renal angle (60.0 %), Pain (48.1 %) and on dysuria (47.1 %). While non-significant effect was found on haematuria (30.0 %). The post-therapy laboratory results in comparison to pre-therapy results showed a decreasing trend in certain parametres while an increasing trend in others. All the parameters, however, remained within their normal limits both in the pre & post-therapy observations. The shwet parpati therapy showed an Overall success rate of 60.0 % in mitigating the problems of mutrashmari and removal/disintegration of calculi.